Effect of saffron addition on the microbiological, physicochemical, antioxidant and sensory characteristics of yoghurt. (13th November 2018) - Gaglio, Raimondo; Gentile, Carla; Bonanno, Adriana; Vintaloro, Lucia; Perrone, Anna; Mazza, Francesca; Barbaccia, Pietro; Settanni, Luca; Di Grigoli, Antonino
Abstract : The impact of added saffron on the characteristics of yoghurt was evaluated during storage. The fat content was lower in the saffron yoghurt. All colour variables were significantly affected by saffron and storage. From the 15th day of storage, bacterial numbers in the saffron yoghurt were higher than those of the control yoghurt. Sensory analysis data suggested that colour, odour and texture impacted consistently on the overall acceptability of the saffron yoghurt. Saffron addition significantly increased polyphenol content and antioxidant activity, providing evidence that the enrichment of natural yoghurt with saffron yields an innovative fermented product useful for supplementing antioxidant dietary intake.